Salivary mucoepidermoid carcinoma: histological variants, grading systems, CRTC1/3‐MAML2 fusions, and clinicopathological features. Issue 4 (14th December 2021) - Nakano, Satsuki; Okumura, Yoshihide; Murase, Takayuki; Nagao, Toshitaka; Kusafuka, Kimihide; Urano, Makoto; Yamamoto, Hidetaka; Kano, Satoshi; Tsukahara, Kiyoaki; Okami, Kenji; Kawakita, Daisuke; Nagao, Toru; et al.
Abstract : Aims: To investigate the histological diversity of salivary mucoepidermoid carcinoma (MEC), its clinicopathological features, and its associations with CRTC1 / 3 ‐ MAML2 fusions. Methods and results: Salivary MEC cases ( n  = 177) were examined for CRTC1 / 3 ‐ MAML2 fusions, histological variants were classified, and tumours were graded according to four different grading systems. Adverse histological features considered to be unusual in MEC were also investigated. Of the 177 MEC cases, 110 were positive for CRTC1 / 3‐MAML2 fusions. The classical variant was the most frequent in the fusion‐positive case group, the fusion‐negative case group, and the total case group. The clear/oncocytic variant was the second most frequent in the fusion‐positive and total case groups. Oncocytic, Warthin‐like and spindle variants were seen in the fusion‐positive case group only. Clear cell, sclerosing, mucinous and central variants were seen in both the fusion‐positive case group and the fusion‐negative case group. No case was classified as a ciliated variant, as a mucoacinar variant, or as a high‐grade transformation. As compared with the classical variant, non‐classical variants were characterised by frequent CRTC1 / 3‐MAML2 fusions and a low clinical stage in all cases. Of the four histological features considered to be unusual in MEC, marked nuclear atypia, frequent mitoses (>10/10 high‐power fields) and extensive necrosis were found independently of the fusion status, and were present in 3–5% of all cases. However, none of the cases showed overt keratinisation. On comparison, the Armed Forces Institute of Pathology and modified Healey grading systems downgraded tumours, the Brandwein system upgraded tumours, and the Memorial Sloan Kettering system provided a moderate means of assessment. Conclusion: Recognition of the histological diversity of MEC, its clinicopathological features and its associations with CRTC1 / 3 ‐ MAML2 fusions is helpful for an accurate diagnosis of this carcinoma.